Large‐Area Solar Cells: Cold Antisolvent Bathing Derived Highly Efficient Large‐Area Perovskite Solar Cells (Adv. Energy Mater. 36/2019). Issue 36 (25th September 2019) - Jang, Gyumin; Kwon, Hyeok‐Chan; Ma, Sunihl; Yun, Seong‐Cheol; Yang, Hyunha; Moon, Jooho
Abstract : In article number1901719, Jooho Moon and co‐workers demonstrate a cold antisolvent bathing method for fabricating highly efficient large‐area perovskite solar cells. This temperature tuned antisolvent bathing adjusts the nucleation and growth of the perovskite materials, leading to large grain‐sized perovskite films with preferred crystal orientation and fewer crystal defects. Reduced recombination and facilitated extraction of photogenerated charge carriers are observed, exhibiting champion efficiency of 18.50%.